Role of visual evoked potentials and optical coherence tomography in the screening for optic pathway gliomas in patients with neurofibromatosis type I. Issue 2 (March 2021) - Vagge, Aldo; Camicione, Paola; Pellegrini, Marco; Gatti, Giulia; Capris, Paolo; Severino, Mariasavina; Di Maita, Marco; Panarello, Simona; Traverso, Carlo E
Purpose: The purpose of the present study was to compare visual function assessment, visual evoked potential, and optical coherence tomography with measurement of retinal nerve fiber layer thickness for the diagnosis of optic pathway glioma in children with neurofibromatosis type 1. Methods: This retrospective observational study included patients with neurofibromatosis type 1 who underwent brain magnetic resonance imaging scan, visual evoked potential study, and peripapillary retinal nerve fiber layer evaluation by optical coherence tomography. Patients were tested with pattern-reversal visual evoked potential and with flash visual evoked potential in case of poor cooperation. Optical coherence tomography was performed with HRA Spectralis (Heidelberg Engineering, Heidelberg, Germany). The area under the curve of receiver operating characteristic curves was used to evaluate the accuracy of each parameter for diagnosing optic pathway glioma. Results: In all, 110 patients with neurofibromatosis type 1 were included in the study. Fifty of them had an optic pathway glioma diagnosed with magnetic resonance imaging, while 60 did not. Global retinal nerve fiber layer thickness demonstrated the highest diagnostic power for discriminating patients with and without optic pathway glioma (area under the curve = 0.758, sensitivity = 65.3%, specificity = 83.3%), followed visual acuity (area under the curve = 0.723, sensitivity = 51.1%, specificity = 91.7%) and P100 of visual evoked potential (area under the curve = 0.712, sensitivity = 69.6%, specificity = 63.8%). Conclusion: The results of the present study showed that the measurement of retinal nerve fiber layer thickness was the most efficient test for discriminating patients with and without optic pathway glioma. Brain magnetic resonance imaging remains the gold standard to confirm the diagnosis of optic pathway glioma. Longitudinal studies are required to define if the early detection of tumors with optical coherence tomography could prevent vision loss and morbidity.